Local Knowledge And Social Capital As Financial Buffers: Understanding MSMEs Risk Mitigation Strategies In Indonesia - Andi Mustika Amin (PT. Maju Malaqbi Makkarana, 2025)
Micro, small, and medium enterprises (MSMEs) in developing countries like Indonesia are highly vulnerable to financial risks yet often lack formal risk-management practices, relying instead on personal experience, intuition, and culturally rooted local practices to navigate financial uncertainty. This study aimed to identify MSME owners' perceptions of financial risks, explore informal mitigation strategies based on local experience and community practices, analyze the influence of cultural norms and social networks, and propose a contextually grounded problem-solving framework. Employing a qualitative research design, the study used in-depth semi-structured interviews, direct observations, and document analysis with MSME owners, and analyzed the data using thematic analysis and triangulation to ensure credibility. The results revealed three primary financial risk-mitigation strategies: adaptive cash-flow management, reliance on social capital and local economic networks, and experiential diversification driven by local market knowledge. The findings demonstrate that MSMEs develop resilience through culturally embedded practices and social structures, confirming that interventions should leverage existing informal mechanisms and integrate culturally compatible tools rather than imposing rigid formal frameworks.